Os conceitos animus e mens no Livro I Tusculanae disputationies de Cícero - Nogueira Borges, Lucas (2015)
The book I Tusculanae Disputationes deals with different soul notions developed by the Greek schools of philosophy by presenting arguments to prove the immortality of the soul. To accomplish this task, Cicero allows a certain philosophical vocabulary in Latin, which creates a parallel to the ψυχή and νοῦς concepts. Cicero plays ψυχή by animus, when you want to designate something more general regarding the substance that remains to death, that is. On the other hand, employs mens in parallel to the platonic and Aristotelic νοῦς as animus intellectual part. However, in Tusc. 1.46, uses animus rather than mens, appearing to be the employment of less careful terms. In view of this problem, this work aims to present the main passages that show the use of animus and mens in Book I of Tusculanas Discussion, discussing the Platonic and Aristotelian foundations used by Cicero to establish the mens concept as part of animus.